FAKTOR–FAKTOR YANG MEMPENGARUHI KINERJA PENYULUH PERTANIAN PEGAWAI NEGERI SIPIL DALAM MELAKSANAKAN TUPOKSI DI KABUPATEN MALANG - Mayor, Fenny Marthina; Pudjiastuti, Agnes Quartina; Suwasono, Son (Fakultas Pertanian, 2019)
Current implementation of agricultural extension is expected to be able to become a facilitator, motivator and regulator of agricultural business actors and be able to build a highly competitive agribusiness system. This study aims to analyze internal and external factor of civil servant agriculture instructors: education, motivation, training, lenght of service, infra-structure, distance to work area, number of target villages, and quantity of target farmer groups and their influence on performance of agricultural instructors civil servant in carrying out TUPOKSI. Research was carried out in seven Technical Implementation Units of Counseling Centers namely: UPT-BP Kec. Singosari, UPT-BP Kec. Lawang, UPT-BP Kec. Karangploso, UPT-BP Kec. Dau, UPT-BP Kec. Pakis, UPT-BP Kec. Pujon, UPT-BP Kec. Pakisaji Malang Regency. Research location was determined purposively and sample was determined based on simple random sampling of 29 civil servant instructors and analyzed with multiple linear regression analysis. The analysis shows that four independent variables have a positive influence on the performance of instructors, namely education, training, work tenure, number of target villages. Performance of agriculture instructors for Civil Servants with likert scale analysis showed very good results with a value of 88,10%. Penyelenggaraan penyuluhan pertanian saat ini diharapkan mampu menjadi fasilitator, motivators dan regulator pelaku usaha pertanian serta mampu membangun sistem agribisnis yang berdaya saing tinggi. Penelitian ini bertujuan untuk menganalisis faktor internal dan eksternal penyuluh pertanian Pegawai Negeri Sipil yang meliputi: pendidikan, motivasi, pelatihan, masa kerja, sarana prasarana, jarak tempuh ke wilayah kerja, jumlah desa binaan dan jumlah kelompok tani binaan serta pengaruhnya terhadap kinerja penyuluh pertanian Pegawai Negeri Sipil dalam melaksanakan TUPOKSI. Penelitian dilakukan di tujuh Unit Pelaksana Teknis Balai Penyuluhan yaitu: UPT-BP Kec. Singosari, UPT-BP Kec.Lawang, UPT BP Kec. Karangploso, UPT BP Kec. Dau, UPT BP Kec. Pakis, UPT BP Kec. Pujon,dan UPT BP Kec. Pakisaji KabupatenMalang. Lokasi penelitian ditentukan secara purposive dan sampel ditentukan berdasarkan simple random sampling sebanyak 29 orang penyuluh PNS dan dianalisis dengan analisis regresi linear berganda. Hasil analisis menunjukkan empat variabel independen memberikan pengaruh positif terhadap kinerja penyuluh yaitu pendidikan, pelatihan, masa kerja dan jumlah desa binaan. Kinerja penyuluh Pegawai Negeri Sipil dengan analisis skala likert menunjukkan hasil yang sangat baik dengan nilai 88,10%.